A novel mechanical design of broken rope protection device for enhancing the safety performances of overhead manned equipment in coal mine. (17th August 2015) - Zhang, Xiaoguang; Zhao, Zhike; Liu, Jigao; Zhao, Yanfang; Xia, Tingting; Da, Jianpu
A novel mechanical design of the broken rope protection device is proposed to enhance the safety performances of the overhead manned equipment. According to the operating characteristics and functional requirements of the overhead manned equipment, a three-dimensional mechanical model of the broken rope protection device was redesigned. Based on the known parameters of the mechanical model, the stress and strength of the main components are readjusted using the statics characteristics of finite element analysis. To ensure the reliability of the control system of the broken rope protection device, the process of people's falling, the response performance of the tension sensor, and the signal extraction of the broken rope are analyzed under different loading and unloading speeds. The working principle of the broken rope protection device is expounded in detail. The experimental results showed that better effect is obtained by the new broken rope protection device, which is characterized by good durability, low investment, and high reliability.